HUBUNGAN ANTARA PENGETAHUAN DENGAN SIKAP IBU-IBU PENGAJIAN NURUL HUDA MEDAN MARELAN TENTANG REBUSAN DAUN KEMANGI (OCINUM SANCTUM) DALAM MENGATASI FLUOR ALBUS - SRI AYU HANDAYANI; YENITA YENITA (JURNAL ILMIAH MAKSITEK, 2022)
The most important period for a woman is the fertile age which lasts up to 15-45 years. Poor female reproductive health problems reach 33% of the total burden of disease suffered by women in the world, one of which is vaginal discharge. The object research are to prove that there is a relationship between knowledge and the attitude of the mothers of Nurul Huda Medan Marelan Recitation regarding Decoction of Basil Leaves (Ocinum sanctum L.) in Overcoming fluor albus. The research method used quantitative research, using a cross sectional approach. The results where the level of knowledge is good with good attitude as many as 33 people (82.5%), the level of knowledge is quite equal to good attitude as much as 2 people (5%), the level of knowledge is sufficient with enough attitude as much as 4 people (10%), and the level of knowledge is sufficient with less attitude as much as 1 person (2.5%). The results of Fisher Exact data analysis showed P = 0.002 (P≤0.05) so that there was a relationship between knowledge and the attitudes of the study mothers of Nurul Huda Medan Marelan about the decoction of basil leaves (Ocinum sanctum L.) in overcoming fluor albus